PENGARUH E-LEADERSHIP MENTOR DI INDUSTRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA MAGANG - Hendrajaya Hendrajaya (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
Universities have a challenge to create competitive human resources in the era of industrialization wave 4.0 which is marked by the global era, the information age and the knowledge era. On the other hand, the Entrepreneurship Internship Program in Higher Education faces the problem of mentor hours in a busy industry, so that the mentor leadership function in guiding student internships in the industry is not effective. The development of information technology and the internet has the potential to facilitate leadership activities that are not limited by space and time. E-Leadership is a leadership activity (as influence, direction and vision) through electronic media. The purpose of this study was to examine the effect of E-Leadership on students' interest in entrepreneurship, either directly or indirectly through mediating variables of perceived feasibility and perceived desire. The research was conducted on 100 final year students at the College of Tourism Economics (STIEPARI) Semarang City who are currently or have participated in an internship program. Data analysis using Structural Equation Model (SEM) with AMOS 16.0 program. The results of this study found that E-Leadership had a positive and significant effect on students' entrepreneurial interest both directly and indirectly through mediating variables of perceived feasibility and perceived desire. The results of this study provide implications for the benefits of information technology and the internet in supporting mentor leadership activities (as influence, direction and vision) in guiding student internships in the industry to be more effective. The originality of this study is to examine the function of mentor leadership in the industry through the electronic media of E-Leadership on perceptions of feasibility, perceptions of desire and interest in entrepreneurship.